2022
DOI: 10.1039/d2ta07048k
|View full text |Cite|
|
Sign up to set email alerts
|

High-performance trimethylamine gas sensors based on defect-engineering MOF-derived ZnO nanoclusters with tunable surface oxygen vacancies

Abstract: In this study, we have successfully fabricated high-performance trimethylamine (TMA) sensor. Defect-engineering (DE) strategy in which two organic ligands, i.e., dicarboxylate and tricarboxylate coordinated with Zn2+ ions simultaneously is adopted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 73 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…O–H and O–CO contribute to the improvement of catalytic and sensing properties. 27,28 Fig. 3(e and f) present the high-resolution XPS spectra of C. It can be observed that C-600 has abundant –CO– and –COO– bonds, indicating that there are enough CO 2 adsorption intermediates on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O–H and O–CO contribute to the improvement of catalytic and sensing properties. 27,28 Fig. 3(e and f) present the high-resolution XPS spectra of C. It can be observed that C-600 has abundant –CO– and –COO– bonds, indicating that there are enough CO 2 adsorption intermediates on the surface of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The O species are oen classied into three categories: Sn-O, O-H and O-C]O. Notably, the percentages of O-H and O-C]O are higher for C-600 than for W-600, probably attributed to the abundant grain boundaries on the material and the lattice defects resulting from C doping and decomposition.O-H and O-C]O contribute to the improvement of catalytic and sensing properties 27,28. Fig.3(e and f) present the high-resolution XPS spectra of C. It can be observed that C-600 has abundant -COand -COObonds, indicating that there are enough CO 2 adsorption intermediates on the surface of the material.…”
mentioning
confidence: 99%
“…37 Other different types of defects have already been characterized by EPR spectroscopy, providing a new insight into gas sensing materials and the corresponding underlying sensing mechanisms (Table 3). [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Table 3 Summary of typical gas sensing materials and the corresponding EPR results…”
Section: Applications Of Epr In Gas Sensorsmentioning
confidence: 99%
“…37 Other different types of defects have already been characterized by EPR spectroscopy, providing a new insight into gas sensing materials and the corresponding underlying sensing mechanisms (Table 3). 38–54…”
Section: Epr In Gas Sensorsmentioning
confidence: 99%
“…[6][7][8][9][10] These sensors are popular, due to their small size and easy operation mechanism, whereby changes in electrical parameters of metal oxides are used as a sensing signal, based on the adsorption of gas molecules on their surface. [6][7][8][11][12][13][14][15][16][17][18] However, to ensure high sensitivity, the sticking coefficient for the adsorption of gases on their surface should be maximized, while keeping the absolute value of the adsorption energy not too high to ensure adsorption/desorption of analytes. Moreover, the presence of different gaseous and volatile organic compounds in the air can cause variations in the conductance (or resistance) of metal oxides, affecting their selectivity to a specic analyte.…”
Section: Introductionmentioning
confidence: 99%